IMPLEMENTATION OF EVIDENCE-BASED PRACTICE AMONG MIDWIFERY STUDENTS IN PADANG CITY - Hindun Mila Hudzaifah; Feri Anita Wijayanti; Feni Andriani; Siska Ilannur Lubis Ilannur Lubis (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
One of the efforts to improve the quality of midwives in order to be able to provide maternal and neonatal services quickly and appropriately by applying Evidence-Based Practice (EBP) to midwifery students. Considering that EBP is a concept in the academic field of midwifery is considered the backbone of quality clinical care. This study aims to determine the practice and use of EBP in midwifery students in the city of Padang, West Sumatra. This study uses a cross-sectional method, uses an online questionnaire Google Forms and is distributed to students through social media to midwifery students whose campus is located in Padang City. The results of the study were from 83 respondents, who had a good level of knowledge in the use of EBP as many as 9 respondents (10.8%), 58 respondents (69.9%), and 16 respondents (19.3%) with a low level of knowledge. As for student attitudes, 49 respondents (59%) had a positive attitude and 34 respondents (41%) had a less supportive attitude in implementing EBP, for practical readiness as many as 14 respondents (16.9%) had high readiness, 60 respondents (72.3%) were in the category of quite ready, and 9 respondents (10.8%) were in the category of not ready in the implementation of EBP. So that it can be concluded that the level of knowledge of midwifery students in the city of Padang in implementing EBP is good and students have a positive attitude and an overview of the readiness of student practice in the category is quite ready.